"Will you stay?" Analysis of place attachment to flyover country. Issue 3 (27th May 2021) - Eshrati, Dorna; Gibson, Huston
ABSTRACT: Wide eyes, a face of surprise, hesitantly asking: "why here?" This is a typical reaction to new international students who come to study in the central agricultural region of the U.S. Stereotypical images have made the central U.S. to be perceived as merely "flyover states" to many people, and surprising destinations when chosen for study, relocation, or even travel. For many who are from rural flyover country communities, finding better job opportunities and more diverse options for living have been convincing enough to move elsewhere, causing considerable population decline. This paper investigates the concept of place attachment in the State of Kansas, USA and shows that despite individuals' emotional bonds to certain aspects of their state, most notably the communal aspect, most intend to leave to seek opportunities elsewhere. This study unfolds community attachment factors to an agricultural region and also identifies the types of attachment people have with it.